2017
DOI: 10.1073/pnas.1621345114
|View full text |Cite
|
Sign up to set email alerts
|

Quon 3D language for quantum information

Abstract: We present a 3D topological picture-language for quantum information. Our approach combines charged excitations carried by strings, with topological properties that arise from embedding the strings in the interior of a 3D manifold with boundary. A quon is a composite that acts as a particle. Specifically, a quon is a hemisphere containing a neutral pair of open strings with opposite charge. We interpret multiquons and their transformations in a natural way. We obtain a type of relation, a string-genus "joint r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…It is shown in [LWJ17] that |GHZ and |M ax are graphic quons, and the corresponding surface tangles are given by Inspired by this observation, we generalize |GHZ and |M ax to n-quons on genus-g surfaces for the MTC C .…”
Section: 2mentioning
confidence: 90%
See 2 more Smart Citations
“…It is shown in [LWJ17] that |GHZ and |M ax are graphic quons, and the corresponding surface tangles are given by Inspired by this observation, we generalize |GHZ and |M ax to n-quons on genus-g surfaces for the MTC C .…”
Section: 2mentioning
confidence: 90%
“…In tensor networks, the |GHZ and |M ax are represented as two trivalent vertices: and . They have been considered as two fundamental tensors in [Laf03], see also [LWJ17,Bia17,CK17].…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…If we apply the sum set estimate to group subfactors and take p, q to be central projections of the group algebra acting on the regular representation, then Equation (5) is equivalent to the following result about representations of a finite group: The SFT has been applied to quantum information in [8,20]. 1 It is shown that the SFT on quons for a unitary modular tensor category is the modular S matrix in [19,20]. Therefore we can apply our results on Fourier analysis to quons and obtain new results about the modular tensor category and the S matrix.…”
Section: Block Mapsmentioning
confidence: 99%
“…Building on a series of results (4-6) Liu, Wozniakowski and Jaffe have recently developed a topological variant of tensor networks which among other results, lead to their discovery of an elegant charged string braiding for the controlled-NOT gate (a.k.a. the Feynman gate) (7).…”
mentioning
confidence: 99%